(3GdQMeI GdZjKjI HGdJQLeI GddjKjIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd HYV Ndbg Ydi HYV OQLGJ CeG HYO , aEf LeGYI ef GdENhGf EdJeShG EaQGO eNJUQ ef CNHGQ abjg GdOjGQ GdeUQjI s
(3BNQgG (B:s
(3agi GdfLGI GdQGhjgG EPG aGXG GfJgi eG LeYg TjNfG TjN GdESdGe MGaX GdYUQ eaJi GdEeGe GdYSbdGfi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs